Detailed and atypical HLA‐E peptide binding motifs revealed by a novel peptide exchange binding assay - Walters, LC; McMichael, AJ; Gillespie, GM (Wiley, 2020)
Diverse SIV and HIV epitopes that bind the rhesus homolog of HLA‐E, Mamu‐E, have recently been identified in SIVvaccine studies using a recombinant Rhesus cytomegalovirus (RhCMV 68‐1) vector, where unprecedented protection against SIV challenge was achieved. Additionally, several Mycobacterial peptides identified both algorithmically and following elution from infected cells, are presented to CD8+ T cells by HLA‐E in humans. Yet, a comparative and comprehensive analysis of relative HLA‐E peptide binding strength via a reliable, high throughput in vitro assay is currently lacking. To address this, we developed and optimized a novel, highly sensitive peptide exchange ELISA‐based assay that relatively quantitates peptide binding to HLA‐E. Using this approach, we screened multiple peptides, including peptide panels derived from HIV, SIV, and Mtb predicted to bind HLA‐E. Our results indicate that although HLA‐E preferentially accommodates canonical MHC class I leader peptides, many non‐canonical, sequence diverse, pathogen‐derived peptides also bind HLA‐E, albeit generally with lower relative binding strength. Additionally, our screens demonstrate that the majority of peptides tested, including some key Mtb and SIV epitopes that have been shown to elicit strong Mamu‐E‐restricted T cell responses, either bind HLA‐E extremely weakly or give signals that are indistinguishable from the negative, peptide‐free controls.